The global environment : institutions, law, and policy / Regina S Axelrod; Stacy D VanDeveer - Axelrod, Regina S.edited by
The new edition of this award-winning volume reflects the latest events in the climate crisis, while providing balanced coverage of the key institutions, issues, laws, and policies in global environmental politics.